Fundamentals of aerodynamics - Anderson, John David; Cadou, Christopher P. (McGraw-Hill series in aeronautical and aerospace engineering, 2024)
The new edition of Fundamentals of Aerodynamics follows in the same tradition as the previous editions: it is for students-to be read, understood, and enjoyed. It is consciously written in a clear, informal, and direct style to talk to the reader and gain their interest in the challenging and yet beautiful discipline of aerodynamics.